Power, Class Consciousness and the Voice of Social Change in Ghamaka Pailaharu (Journal of Bhuwanishankar, 2024)
Dhanush Chandra Gautam, with his literary name Dha Cha Gotame, composed the novel Ghamka Pailaharu in Tarai setting, reflecting upon the social reality as a driving force. Authors reflect the social reality in multiple ways. Gotame’s social picture aligns with the reality of class structure. This research article aims to examine how the author has presented the social reality in this novel as the central problem of this research. It applies the Marxist theory of class consciousness, power and the social change as the tool of the research. With the details of the construction of railroad networking, the author gives the social picture of the mixed community in an imagined city as the representation of people from different strata. Their relationship gives a class structure of the capitalist or aristocrats and the citizens of the unmentioned or nameless society. It can be further observed as self-called civilized and uncivilized ones. The society as depicted in the novel is power centric and is the combination of the class-based structure.